Theoretical and legal issues of the calculations - Хірс, Яніна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
The article is devoted to disclosure of nature, legal features and content of payment relations. The basictheoretical principles concerning payments have been stated. Existing deficiency in this area of law have been identified and specific proposals have been defined to eliminate them.